The Influence of Implementing Islamic Business Ethics, Product Quality, and Islamic Service Quality on Consumer Loyalty with Consumer Satisfaction as an Intervening Variable (Study on Consumers of Cafe Teras Angkringan Benkemebul) - Eka Setiawan; Endah Nur Fitiriani (Journal of Islamic Enterpreneurship and Management, 2024)
The Influence of Implementing Islamic Business Ethics, Product Quality, and Islamic Service Quality on Consumer Loyalty with Consumer Satisfaction as an Intervening Variable (Study on Consumers of Cafe Teras Angkringan Benkemebul) Thesis. Faculty of Islamic Economics and Business. S1 Sharia Economics. Salatiga State Islamic University. Supervisor: Endah Nur Futriyani, M. M. This research aims to determine the effect of implementing Islamic Business Ethics, Product Quality, and Islamic Service Quality on Consumer Loyalty with Consumer Satisfaction as an Intervening Variable (Study on Consumers of Cafe Teras Angkringan Benkemebul) This type of research is quantitative research with the consumer population of Cafe Teras Angkringan Benkemebul. The sampling technique in this research used non-brobability sampling, totaling 100 respondents. The analytical methods used include validity tests, reality tests, classical assumption tests, hypothesis tests and path analysis tests. This research uses the SPSS data analysis tool. The research results show that Islamic business ethics, product quality and Islamic service quality have a positive but not significant effect on consumer loyalty. Consumer satisfaction has a positive and significant effect on consumer loyalty. Islamic business ethics has a positive but not significant effect on consumer satisfaction. Product quality and Islamic service quality have a positive and significant effect on consumer satisfaction. Consumer satisfaction is unable to mediate the influence of Islamic business ethics and product quality on consumer loyalty. Consumer satisfaction is able to mediate the quality of Islamic services on consumer loyalty.